RETRACTED: The technology of improving the drying process of cotton raw materials in a drum dryer - Khurmamatov Abdugaffor; Umarov Elmurod; Matkarimov Shukhrat; Tojiboyev Bobur (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001